Hubungan Antara Persepsi Terhadap Komunikasi Atasan Dengan Komitmen Organisasi Di PT. X Karanganyar - Raharjo, Wida Septian; , Susatyo Yuwono, S.Psi., M.Si, Psi (2017)
The purpose of this research that is to know correlation between perception toward superiors communication with commitment organization. Hypothesis is that there is a positive correlation between perception communication superiors with commitment organization. A subject in this study are employees part sewing PT. X. The number of subject to research is 150 employees with the methods the sample collection clusters random sampling. Research methodology uses the quantitative. Using a technique data analysis correlation non parametric the spearman's rho. The results of analysis data show that there was a positive correlation very significant between perception toward superiors communication with commitment organization, seen from value r of 0,509 with p = 0,000 (p<0,01). The result of categorisation known that the variable perception toward superiors communication having rerata empirical of 87,67 and rerata hipotetik by 80 which means are being. Variable commitment the organisation have rerata empirical of 53,22 and rerata hipotetik of 60 which means are being. Contributions perception toward superiors communication of 25,9%. The rest of 74,1% influenced by other factors out perception toward communication. Key word : perception toward superiors communication, commitment organization